Optical Coherence Tomography Angiography of Punctate Inner Choroidopathy - Blake M. Hampton; Christopher M. Aderman; Harry W. Flynn; Jayanth Sridhar (Case Reports in Ophthalmological Medicine)
Purpose. To report a case of bilateral choroidal neovascularization (CNV) in punctate inner choroidopathy (PIC) visualized utilizing optical coherence tomography angiography (OCT-A). Methods. Case report. Results. A 29-year-old woman presented with new visual symptoms in both eyes. Fundoscopic exam revealed bilateral multifocal, small, well-defined lesions consistent with PIC. Optical coherence tomography demonstrated subretinal fluid and retinal pigment epithelium detachments (RPEDs) in both eyes. OCT-A revealed bilateral abnormal increased flow within the RPEDs consistent with CNV. Fluorescein angiography confirmed the presence of bilateral CNV. Conclusion. CNV secondary to PIC may be identified using noninvasive optical coherence tomography angiography.